A Panel Data Study of Physicians' Labor Supply: The Case of Norway - Badi H. Baltagi; Espen Bratberg; Tor Helge Holmås (Center for Economic Studies and ifo Institute (CESifo), 2003)
Physicians are key personnel in a sector which is important due to its size as well as the quality of service it provides. We estimate the labor supply of physicians employed at hospitals in Norway, using personnel register data merged with other public records. A dynamic labor supply equation is estimated using a sample of 1303 physicians observed over the period 1993-97. The methods of estimation are GMM and system GMM. We reject the static model in favor of a dynamic model and obtain a long-run wage elasticity of about 0.55. This is considerably higher than previously estimated for physicians, in particular for those who are not self-employed.
Keywords: 330; physicians; labor supply; dynamic panel data